The reality of medical and health monitoring among junior football players - berdjem, Redouane; belouni, Abdelhalim (sports creativity, 2025)
Since ancient times, scientists have shown great importance to health topics in general, believing that a sound mind is in a sound body, and that a sick person cannot serve society adequately. Thus, the qualifications of medicine and health sciences alike have contributed to creating a new generation that is strong in structure, resisting the conditions of life. Interest in sports has increased because it has become one of the most important features of modern civilization. Sports medicine has emerged, which is the field of taking care of the athlete’s health, maintaining it, and monitoring it. Since sports clubs are considered a field in which the goals of sports activity are carried out, and since the player is in dire need of maintaining it. Undoubtedly, health education is one of the duties of coaches, managers, and team presidents. Therefore, those concerned must maintain the health and safety of their players and protect them from all causes of accidents through various means. Among these means is regular medical examination, which can help maintain the safety and well-being of players and protect them from accidents and illnesses that could have chronic consequences and a definite decline in their performance. It also allows the coach, management, and medical staff to protect players from injuries and to avoid liability for accidents that may befall them. Therefore, it is essential that sports medicine be integrated into football. Accordingly, this work is directed to all those concerned with the health of players within sports clubs, namely the coach and team president, to ensure the safety of players and protect them from all dangers that could affect their proper functioning. In addressing this topic, we aim to shed light on the reality of medical and health monitoring on the field and its role in selecting the most suitable and medically fit players for football, as well as to understand the reasons for the lack of medical follow-up and monitoring of young players.